Dental pulp stem cells grown on dental implant titanium surfaces: An in vitro evaluation of differentiation and microRNAs expression. Issue 5 (9th February 2016) - Iaculli, Flavia; Di Filippo, Ester Sara; Piattelli, Adriano; Mancinelli, Rosa; Fulle, Stefania
Abstract: The surface roughness of dental implants influences the proliferation and differentiation rate of adult mesenchymal stem cells (MSCs). The aim of the present study was to evaluate whether specifically treated titanium implant surfaces influenced human dental pulp stem cells (DPSCs) differentiation in an osteogenic pattern through modulation of microRNAs expression. The degree of differentiation was evaluated after 7, 14, and 21 days, through the expression of microRNAs characterizing the osteogenesis (miR‐133 and miR‐135), of Runx2 and Smad5 (key factor transcriptions associated with osteoblast differentiation) and Osteocalcin, marker for the bone formation process. DPSCs were cultured on sandblasted and acid‐etched titanium disks, with (Test) or without the presence of ions (Control). Early differentiation of DPSCs cultured on titanium could be detected at all the evaluated time points, respect to cells grown alone. Moreover, the Test surfaces seemed to induce a more marked cells differentiation. The obtained results demonstrated that microRNAs played a pivotal role in the differentiation of MSCs and could be used as marker of osteogenic differentiation. Furthermore, the evaluated ionized sandblasted and acid‐etched surface seemed to markedly enhance the development of osteoblast cells. A faster osseointegration could be achieved in the presence of specifically treated implant surfaces, promising encouraging clinical outcomes. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 953–965, 2017.